2020
DOI: 10.1136/neurintsurg-2020-016048
|View full text |Cite
|
Sign up to set email alerts
|

Middle meningeal artery embolization reduces the post-operative recurrence rate of at-risk chronic subdural hematoma

Abstract: BackgroundEmbolization of the middle meningeal artery (MMA) has emerged as a potential treatment of chronic subdural hematomas (CSDHs).ObjectiveTo evaluate the impact on recurrence rate of postsurgical embolization of CSDH in patients with a higher than average risk of recurrence.MethodsA monocentric retrospective study was performed on retrospectively collected data. From March 2018 to December 2019, embolization of the MMA was proposed as an adjunct postoperative treatment after burr-hole surgery in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 28 publications
1
52
1
Order By: Relevance
“…These were the only studies that reported a control group where patients underwent surgical drainage for their CSDH. [11][12][13][14] The details of these studies are given in the Table 1. The studies were conducted in Korea 11,12 and France.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These were the only studies that reported a control group where patients underwent surgical drainage for their CSDH. [11][12][13][14] The details of these studies are given in the Table 1. The studies were conducted in Korea 11,12 and France.…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in Korea 11,12 and France. 13,14 Quality of evidence Quality of evidence was generally low. All the studies included had a mixed prospective intervention group and retrospective historical control group with one randomized control trial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 – 10) In a previous study, 4 of the 89 patients (4%) in the MMAE group required burr hole surgery for CSDH recurrence, significantly less than the 24 of the 174 patients (14%) in the control group ( P = 0.02, odds ratio: 95% confidence interval 0.28: 0.07–0.86). 9) Exponential increases in utilization of MMAE for CSDH treatment in recent years in USA. 11) In Japan, the number of carotid artery angioplasty with stenting (CAS) procedures exceeds that of carotid endarterectomy procedures.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a significant improvement in neurological disability scores, as measured by the modified Rankin scale. Similarly, Shotar et al found that postsurgical embolization of the MMA reduced the recurrence rate of cSDH from 14% to 4% [ 37 ].…”
Section: Reviewmentioning
confidence: 99%